Effect of Streptomycin-Penicillin and Gentamicin-Tylosin- Lincomycin-Spectinomycin on the Quality and Bacterial Load of Frozen-Thawed Semen of Surti Buffalo Bull - Nandan, Devki; Gaur, Mitesh; Sharma, Deepak; Pargi, Kalpesh; Ram, Vachna (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study evaluated the effect of two different antibiotic combinations SP (streptomycin, penicillin) and GTLS (gentamicin, tylosin, lincomycin and spectinomycin), as antibiotic regimens in TCFY (Tris-citric acid-fructose-yolk) semen extender on Surti buffalo bull semen. A total of 12 ejaculates from 6 bulls were collected. After evaluation of the dilution rate, the fresh semen was divided into three parts. Each part of the semen was extended upto 80 million spermatozoa/mL. One control group (part 1) was maintained with no antibiotics, while antibiotic combination SP and GTLS was added into part 2 and part 3 at the concentration of streptomycin 1000 µg/mL, penicillin 1000 IU/mL (Treatment-1), and gentamicin 500 µg/mL, tylosin 100 µg/mL, lincomycin 300 µg/mL and spectinomycin 600 µg/mL (Treatment-2). Pre-freeze and post-thaw microbial load (CFU/mL) and sperm abnormalities were found to be significantly (p<0.05) lower, whereas individual progressive sperm motility, live sperm percentage and HOS responsive spermatozoa were significantly (p<0.05) higher in semen samples treated with antibiotic combinations SP and GTLS in comparison to control. Further, the GTLS had a significantly (p<0.05) lower bacterial load at the pre-freeze and post-thaw stage as compared to SP. However, the observations on sperm parameters with SP and GTLS were statistically similar. It was concluded that SP and GTLS in semen extender show significant improvement in pre-freeze and post-thawed semen quality, statistically both at par as compared to control, and more efficiently reduced the bacterial load compared to SP and non-added control suggesting its preference for use in bovine frozen semen extender.